Revisão taxonômica do gênero Imparfinis sensu stricto - Lopes, Maridiesse Morais (2020)
ABSTRACT Among the Neotropical catfishes of order Siluriformes, the Heptapteridae family corresponds to a monophyletic group sustained by five synapomorphies. Just over half of the genera recognized under the Heptapteridae are grouped in a monophyletic as